2007
DOI: 10.1007/s00213-007-1014-6
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neurochemical characterization of mice deficient in the phosphodiesterase-4B (PDE4B) enzyme

Abstract: The present studies demonstrate decreased striatal DA and 5-HT activity in the PDE4B knockout mice associated with decreased prepulse inhibition, decreased baseline motor activity, and an exaggerated locomotor response to amphetamine. These data further support a role for PDE4B in psychiatric diseases and striatal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 75 publications
4
73
1
Order By: Relevance
“…Using mice deficient in PDE4B, it has been demonstrated that this subtype plays a critical role in lipopolysaccharide-induced signaling and inflammatory responses (Ariga et al, 2004;Jin et al, 2005a). Most recently, it has been shown that PDE4B is required for the antipsychotic effect of rolipram (Siuciak et al, 2007), which is consistent with the association of this subtype with schizophrenia (Millar et al, 2005). Nevertheless, little is known about the CNS function of PDE4B.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Using mice deficient in PDE4B, it has been demonstrated that this subtype plays a critical role in lipopolysaccharide-induced signaling and inflammatory responses (Ariga et al, 2004;Jin et al, 2005a). Most recently, it has been shown that PDE4B is required for the antipsychotic effect of rolipram (Siuciak et al, 2007), which is consistent with the association of this subtype with schizophrenia (Millar et al, 2005). Nevertheless, little is known about the CNS function of PDE4B.…”
Section: Discussionmentioning
confidence: 82%
“…While the roles of these variants are still not known, recent studies using mice deficient in PDE4B have shown that this subfamily plays a complementary role in the control of neutrophil function (Ariga et al, 2004) and is required for antipsychotic effects of rolipram (Siuciak et al, 2007). In addition, PDE4B also is involved in schizophrenia by interacting with the DISC1 gene, a candidate susceptibility factor for schizophrenia (Clapcote et al, 2007;Millar et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…First, it is not unanimously accepted that amphetamineinduced hyperactivity is a valid model of manic behavior. Second, there is evidence that rolipram (discussed above) also decreases methamphetamineinduced hyperlocomotion (Siuciak et al, 2007).…”
Section: Glycogen Synthase Kinase-3 (Bipolar Disorder and Major Deprementioning
confidence: 99%
“…PDE4 has been implicated as a player in the pathophysiology of schizophrenia and mood disorders through linkage studies as well as through its interaction with the schizophrenia candidate gene disrupted in schizophrenia 1 (DISC1) (12)(13). Genetic deletion of PDE4 isoforms in mice affects cognitive, depressive-related, and anxiety-related behaviors (14)(15)(16). Furthermore, PDE4 inhibitors improve sensorimotor gating, strengthen memory, and reduce depressive-related behaviors in rodents (e.g., [17][18][19][20][21][22][23].…”
Section: Pde11a Ko Mice Show a Subset Of Phenotypes Associated Withmentioning
confidence: 99%
“…If PDE11A is expressed only in a subpopulation of cells within a discrete subregion of the brain, one might not expect to detect expression when analyzing samples prepared from an entire brain (region). Evidence implicating other PDE families in brain function and psychiatric disease (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), along with a recent report linking PDE11A to major depressive disorder and antidepressant response (31), suggest that it is important to understand the role of PDE11A in the brain. Using in situ hybridization, quantitative real-time PCR, and Western blot, we clarify here where in the brain PDE11A is expressed and, by using PDE11A-deleted mice, we demonstrate a role for PDE11A in brain function.…”
mentioning
confidence: 99%